Can biochar fillers advance the properties of composites? Early-stage characterization and life cycle assessment of novel polyamide/biochar biocomposites - Baniasadi, Hossein; Äkräs, Laura; Paganelli, Zoe; Dammann, Nele; Abidnejad, Roozbeh; Lipponen, Sami; Silvenius, Frans; Vahvaselkä, Marjatta; Ilvesniemi, Hannu; Seppälä, Jukka; Niskanen, Jukka (Elsevier, 2025)
In response to growing environmental concerns, this study explores the potential of polyamide 1010 (PA1010) and biochar biocomposites as a sustainable solution in polymer engineering. The research addresses the gap in reinforcing biocomposites with biochar, demonstrating enhanced physical properties and reduced environmental impact. Scanning electron microscopy (SEM) revealed excellent biochar dispersion and strong adhesion with the PA1010 matrix. Mechanical testing showed significant improvements, including a 44 % increase in tensile strength and a 110 % increase in tensile modulus. Thermal stability also improved, increasing decomposition temperature from 460 °C to 474 °C. Additionally, dynamic mechanical analysis (DMA) and rheology tests confirmed increased stiffness and flow resistance. Life cycle assessment (LCA) highlighted a 65 % reduction in carbon footprint, indicating the environmental benefits of these biocomposites. These findings position PA1010/biochar biocomposites as promising materials for sustainable applications in engineering, particularly in industries seeking to reduce environmental impact while enhancing performance.
Keywords: Polyamide 1010; biochar; biocomposite; characterization; life cycle assessment